The Differences in Serum Quantitative Specific IgE Levels Induced by Dermatophagoides pteronyssinus, Dermatophagoides farinae and Blomia tropicalis Sensitization in Intermittent and Persistent Allergic Asthma - Agus Joko Susanto; Iris Rengganis; Cleopas M Rumende; Kuntjoro Harimurti (Interna Publishing, 2018)
Background: house dust mites (HDM) are an important inhalant allergen in allergic asthma. However, molecular diagnostic study of specific IgE to HDM allergens has not been done in Indonesia. In addition, the association of quantitative specific IgE measurement with asthma severity has not been investigatedd. This study aimed to investigate the difference of serum quantitative specific IgE levels induced by Dermatophagoides (D.) pteronyssinus, D. farinae and Blomia tropicalis sensitization in intermittent and persistent allergic asthma. Methods: this was a cross-sectional study on adult allergic asthma patients who were invited for serum specific IgE testing. This study was a part of a larger study within the Division of Allergy and Immunology, Cipto Mangunkusumo Hospital. Asthma severity was defined based on Global Initiative on Asthma (GINA) 2015 criteria and were grouped as intermittent or persistent. Quantitative specific IgE testing was done on blood serum using a multiple allergosorbent test (Polycheck Allergy, Biocheck GmbH, Munster, Germany). The HDM allergens tested were D. pteronyssinus, D. farinae, and Blomia tropicalis. Difference between two groups were analyze using Mann-Whitney test. Results: a total of 87 subjects were enrolled in this study; 69 (79.3%) were women. Mean patients' age was 40, 2 years. Sixty-three (72.4%) subjects had asthma and allergic rhinitis. Fifty-eight (66.7%) subjects were classified as persistent asthma. The prevalence of sensitization was 62.1% for D. farinae, 51.7% for D. pteronyssinus, and 48.3% for Blomia tropicalis. The median of specific IgE levels were significantly higher in persistent asthma compares to intermittent asthma induced by D. farinae (median 1.30 vs. 0.0 kU/L; p=0.024) and B. tropicalis (median 0.57 vs. 0.0 kU/L; p=0.015) sensitization. Level of Specific IgE  D. pteronyssinus was also to be higher in persistent asthma than the level measured in intermittent asthma (0.67 vs. 0.00 kU/L; p=0.066). Conclusion: Sensitization of HDM allergens was shown to be highest for D. farinae 62.1%, followed by D. pteronyssinus 51.7% and Blomia tropicalis 48.3%. Specific IgE level induced by D. farinae and Blomia tropicalis sensitization were significantly higher in patients with persistent asthma compared to intermittent asthma, whereas specific IgE level induced by D. pteronyssinus sensitization was higher in persistent asthma although not statistically significant.